Benzodiazepines utilization in Brazilian older adults: a population-based study - Freire, Marina de Borba Oliveira; Silva, Bruna Gonçalves Cordeiro da; Bertoldi, Andréa Dâmaso; Fontanella, Andréia Turmina; Mengue, Sotero Serrate; Ramos, Luiz Roberto; Tavares, Noemia Urruth Leão; Pizzol, Tatiane da Silva Dal; Arrais, Paulo Sérgio Dourado; Farias, Mareni Rocha; Luiza, Vera Lucia; Oliveira, Maria Auxiliadora; et al. (Revista de Saúde Pública, 2022)
OBJECTIVE: To evaluate the utilization of benzodiazepines (BZD) in Brazilian older adults, based on the Pesquisa Nacional de Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM - National Survey of Access, Use and Promotion of Rational Use of Medicines). METHODS: The PNAUM is a cross-sectional study conducted between 2013 and 2014, representing the Brazilian urban population. In the present study, we included 60 years or older (n = 9019) individuals. We calculated the prevalence of BZD utilization in the 15 days prior to survey data collection according to independent variables, using a hierarchical Poisson regression model. A semistructured interview performed empirical data collection (household interview). RESULTS: The prevalence of BZD utilization in the older adults was 9.3% (95%CI: 8.3–10.4). After adjustments, BZD utilization was associated with female sex (PR = 1.88; 95%CI: 1.52–2.32), depression (PR = 5.31; 95%CI: 4.41–6, 38), multimorbidity (PR = 1.44; 95%CI: 1.20–1.73), emergency room visit or hospitalization in the last 12 months (PR = 1.42; 95%CI: 1.18–1.70 ), polypharmacy (PR = 1.26; 95%CI: 1.01–1.57) and poor or very poor self-rated health (PR = 4.16; 95%CI: 2.10–8.22). Utilization was lower in the North region (PR = 0.18; 95%CI: 0.13–0.27) and in individuals who reported abusive alcohol consumption in the last month (PR = 0.42; 95%CI: 0.19–0.94). CONCLUSION: Despite contraindications, results showed a high prevalence of BZD utilization in older adults, particularly in those with depression, and wide regional and sex differences.